Production of biodiesel using the microwave technique - Shakinaz A. El Sherbiny (Journal of Advanced Research, 2010)
Biodiesel production is worthy of continued study and optimization of production procedures because of its environmentally beneficial attributes and its renewable nature. Non-edible vegetable oils such as Jatropha oil, produced by seed-bearing shrubs, can provide an alternative and do not have competing food uses. However, these oils are characterized by their high free fatty acid contents. Using the conventional transesterification technique for the production of biodiesel is well established. In this study an alternative energy stimulant, “microwave irradiation”, was used for the production of the alternative energy source, biodiesel. The optimum parametric conditions obtained from the conventional technique were applied using microwave irradiation in order to compare the systems. The study showed that the application of radio frequency microwave energy offers a fast, easy route to this valuable biofuel with the advantages of enhancing the reaction rate (2 min instead of 150 min) and of improving the separation process. The methodology allows for the use of high free fatty acid content feedstock, including Jatropha oil. However, this emerging technology needs to be further investigated for possible scale-up for industrial application.